The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4014/mbl.1911.11009
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Macamide B Content and Muscle Cell Protection of Maca (Lepidium meyenii) Extracted Using Ultrasonification-Assisted Extraction

Abstract: This study aims to evaluate the efficacy of the Ultrasonication-Assisted (UA) extraction on the functionality of the herbaceous biennial plant maca (Lepidium meyenii). The specific objectives include comparison of the antioxidant activities among various maca extracts, determination of the macamide B content of the extracts, and in vitro evaluation of maca on cell viability and creatine kinase (CK) activity. The antioxidant activities of the water, ethanol, and UA extracts were compared by determining the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The present study showed the in vitro effects of L. meyenii on the sperm parameters of capacitated frozen-thawed bull semen. Several studies have shown that Maca has an effect on seminal quality in humans [5,12,32], mice [1, 2, 8-10], and stallions [6,17] that is related to its antioxidant capacity [4,11,[33][34][35][36] because, during cryopreservation, sperm is damaged by OS [18][19][20][21]. In addition to the high concentration of antioxidants, L. meyenii contains several secondary metabolites [3,14,22,23], which help in keeping ROS levels low [14,17].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed the in vitro effects of L. meyenii on the sperm parameters of capacitated frozen-thawed bull semen. Several studies have shown that Maca has an effect on seminal quality in humans [5,12,32], mice [1, 2, 8-10], and stallions [6,17] that is related to its antioxidant capacity [4,11,[33][34][35][36] because, during cryopreservation, sperm is damaged by OS [18][19][20][21]. In addition to the high concentration of antioxidants, L. meyenii contains several secondary metabolites [3,14,22,23], which help in keeping ROS levels low [14,17].…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, Leiva-Revilla et al (2022) could be reported that in bovine semen the four dilutions of maca extract at 0, 1, 10, and 100 mg/mL post-thawing incubation for 24 hours indicated rectilinear motility up to 49,60,53 and 48 %,normal 88,90,87 and 87 %,intact live acrosome 21,25,40 and 30%,livability 22,25,41 and 30% and normal DNA 90.60,92.29,91.35 and 91.44%,respectively. Then, the best of aqueous extract of maca on ram semen extenders during the short-term storage at 5 °C for 5 days may be related to antioxidant activity. In this context, Buyanbadrakh et al (2020) who revealed that macaridine, macaene, macamides and alkaloids in maca has freeradical scavenging capacity and increase the levels of superoxide dismutase and glutathione. Also, amino acid in maca like arginine showed an improvement in sperm quality.…”
Section: Discussionmentioning
confidence: 99%